2023
DOI: 10.32895/ump.mpr.7.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep quality and internet addiction in high school students

Abstract: Background: Internet addiction and poor sleep quality are two types of common mental health disorders among high school students. This study was conducted to determine the prevalence of poor sleep quality and its association with internet addiction in high school students. Methods: A cross-sectional study was conducted on 820 high school students in Dong Hoa town, Phu Yen province in April 2021. The students were requested to fill out a structured questionnaire. internet addiction was evaluated by the short v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This may be explained by different coping strategies for stress or bad emotions. Studies on addiction have shown that both genders can be affected, with some research indicating higher rates of addiction among females [ 21 , 40 , 41 ]. It has been consistently observed in various studies that males exhibit significantly higher scores of internet addiction as compared to females [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by different coping strategies for stress or bad emotions. Studies on addiction have shown that both genders can be affected, with some research indicating higher rates of addiction among females [ 21 , 40 , 41 ]. It has been consistently observed in various studies that males exhibit significantly higher scores of internet addiction as compared to females [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows a higher percentage of young people with sleep-related problems, where 46.6% of the sample was classified as having daytime sleepiness [29]. On the other hand, there are several studies analyzing daytime sleepiness with different instruments [52,53], but the results show that excessive daytime sleepiness in adolescents is a growing public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with some findings [50,54] where there were no significant differences between males and females, using the IAT. However, the literature shows several inconsistencies in the effects, since other studies [16,53] using the same instruments have produced results showing a higher prevalence of addiction in females compared to males. On the other hand, several studies have found that males have higher internet addiction scores than females, using different instruments: Young's internet addiction test [49] and Young's 10-item internet addiction test [55].…”
Section: Discussionmentioning
confidence: 99%